Lusting, learning and lasting in school: sexual debut, school performance and dropout among adolescents in primary schools in Karonga district, northern Malawi. Issue 5 (September 2019) - Sunny, Bindu S.; DeStavola, Bianca; Dube, Albert; Price, Alison; Kaonga, Allan M.; Kondowe, Scotch; Crampin, Amelia C.; Glynn, Judith R.
Abstract: Age at sexual debut is known to have implications for future sexual behaviours and health outcomes, including HIV infection, early pregnancy and maternal mortality, but may also influence educational outcomes. Longitudinal data on schooling and sexual behaviour from a demographic surveillance site in Karonga district, northern Malawi, were analysed for 3153 respondents between the ages of 12 and 25 years to examine the association between sexual debut and primary school dropout, and the role of prior school performance. Time to dropout was modelled using the Fine and Gray survival model to account for the competing event of primary school completion. To deal with the time-varying nature of age at sexual debut and school performance, models were fitted using landmark analyses. Sexual debut was found to be associated with a five-fold increase in rate of subsequent dropout for girls and a two-fold increase in dropout rate for boys (adjusted hazard ratio [aHR] of 5.27, CI 4.22–6.57, and 2.19, CI 1.77–2.7, respectively). For girls who were sexually active by age 16, only 16% ultimately completed primary schooling, compared with 70% aged 18 or older at sexual debut. Prior to sexual debut, girls had primary completion levels similar to those of boys. The association between sexual debut and school dropout could not be explained by prior poor school performance: the effect of sexual debut on dropout was as strong among those who were not behind in school as among those who were overage for their school grade. Girls who were sexually active were more likely to repeat a grade, with no effect being seen for boys. Pathways to dropout are complex and may differ for boys and girls. Interventions are needed to improve school progression so children complete primary school before sexual debut, and to improve sex education and contraception provision.